Molecular targets in acromegaly - Labadzhyan, Artak; Melmed, Shlomo (Frontiers in Endocrinology, 2022)
Molecular therapeutic targets in growth hormone (GH)-secreting adenomas range from well-characterized surface receptors that recognize approved drugs, to surface and intracellular markers that are potential candidates for new drug development. Currently available medical therapies for patients with acromegaly bind to somatostatin receptors, GH receptor, or dopamine receptors, and lead to attainment of disease control in most patients. The degree of control is variable: however, correlates with both disease aggressiveness and tumor factors that predict treatment response including somatostatin receptor subtype expression, granulation pattern, kinases and their receptors, and other markers of proliferation. A better understanding of the mechanisms underlying these molecular markers and their relationship to outcomes holds promise for expanding treatment options as well as a more personalized approach to treating patients with acromegaly.